A bridge over troubled water: Flooding shocks and supply chains - Gert Bijnens; Mariano Montoya; Stijn Vanormelingen (National Bank of Belgium, 2024)
This paper estimates how the impact of a natural disaster propagates through the production network. More precisely, we look at the excessive rainfall in the summer of 2021 that caused large areas to be severely flooded in Belgium. We first look at the direct effects on firms active in the flooded areas and find substantial negative effects on sales and employment. Next, we investigate how these shocks propagate through the network, thereby differentiating explicitly between upstream and downstream linkages. Our results show that the floods had a strong negative impact on the performance of firms active in the area. In terms of the supply chain effects, we find negative and persistent effects on sales for firms with upstream exposure.
Keywords: D57; L25; Q54; R11; L14; 330; Flooding; climate change; firms; production network